Oesophageal cancer and Kaposi's Sarcoma in Malawi: a comparative analysis - Mlombe, Yohannie (The Medical Association Of Malawi, 2009)
Given that oesophageal cancer (OC) is common in Malawi and its outcome is so dismal, would it be pragmatic to promptly mitigate the effects of smoking, alcohol and aflatoxins rather than seek a higher degree of local evidence for their role in OC? We retrospectively analysed a total of 13,217 OC and Kaposi's sarcoma (KS) cases as recorded in the Malawi National Cancer Registry from 1985 to February, 2006. We found no OC clustering to suggest a role for culturally variable habits like smoking, alcohol, maize use and maize storage in the country. It may be that drinking and eating hot foods physically damages the oesophageal mucosa, this is in line with work recently reported from Asia. We also found that OC numbers have risen in line with KS (and HIV) suggesting a link between these conditions.